BASIC ELECTRICAL WELDING / ELECTRIC WELDING TRAINING IN LABORATORY OF EDUCATION ENGINEERING UNIVERSITY OF PALANGKA RAYA - Wiyogo; Fritman Dalito (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
The training activities are very important because they are useful to increase knowledge or skills, especially for those who are preparing to enter the workforce. Whereas those who are already working will aim to keep the capability maintained. To carry out these activities carried out at the Laboratory of Mechanical Engineering Education Faculty of Teacher Training and Education, University of Palangka Raya. Through community service activities carried out in Higher Education in line with the functions and objectives mandated in Law Number 12 of 2012 Article 4 paragraph 3;